METODE MULTI ATTRIBUTE DECISION MAKING DENGAN MODEL SIMPLE ADDITIVE WEIGHTING SEBAGAI PENDUKUNG KEPUTUSAN PEMBERIAN PINJAMAN - Alhibarsyah Alhibarsyah (Industrika : Jurnal Ilmiah Teknik Industri, 2020)
Decision support systems are used to solve a problem that is commonly done by users and industry, in this case one of the application of a decision support system in providing loans to cooperative members. Judging from the form of business, cooperatives are one of the community financial institutions that are formed and are not only business-oriented, but social factors are very strongly applied. Because the cooperative was formed to help and prosper its members, such as saving and borrowing (credit) from its members. In this study, decision making is used to help support the selection of loan applications for members. There are several types of decision models that are integrated in a Decision Support System such as statistical models, optimization models, heuristic models and multi-criteria / attribute models. The Simple Additive Weighting (SAW) method is used with the basic concept of finding the weighted sum of the performance ratings on each criterion. According to the MADM model which is used as decision support who can select criteria in determining the eligibility of members in receiving loans (credit). The system provides a solution in determining loan recommendations to prospective borrowers in cooperatives. The system is only able to represent 10 sample members as a reference in calculating credit lending.